2020
DOI: 10.1051/e3sconf/202014604003
|View full text |Cite
|
Sign up to set email alerts
|

Local Capillary Pressure Estimation Based on Curvature of the Fluid Interface – Validation with Two-Phase Direct Numerical Simulations

Abstract: With the advancement of high-resolution three-dimensional X-ray imaging, it is now possible to directly calculate the curvature of the interface of two phases extracted from segmented CT images during two-phase flow experiments to derive capillary pressure. However, there is an inherent difficulty of this image-based curvature measurement: the use of voxelized image data for the calculation of curvature can cause significant errors. To address this, we first perform two-phase direct numerical simulations to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, this was not appropriate for our cases—computed curvatures away from the solid wall do not necessarily give an accurate estimation as shown in Figure 9. This was also concluded from our other test cases reported in Akai et al [32].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, this was not appropriate for our cases—computed curvatures away from the solid wall do not necessarily give an accurate estimation as shown in Figure 9. This was also concluded from our other test cases reported in Akai et al [32].…”
Section: Resultssupporting
confidence: 89%
“…We also tested constrained Gaussian smoothing for these cases; however, it was found that constrained Gaussian smoothing was inadequate resulting in larger errors when the curvature was small (contact angles close to 90). We refer to Akai et al [32] for a further detailed comparison of smoothing methods. Furthermore, Li et al [11] used an average weighted by the distance from the solid to obtain a representative curvature value for a patch of the interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation